2024
DOI: 10.1002/adsu.202300571
|View full text |Cite
|
Sign up to set email alerts
|

Operando Combined SAXS/XRD/XAFS Measurements of Lithium Conversion Battery

Yasuhiro Takabayashi,
Koji Kimura,
Takeshi Miyazaki
et al.

Abstract: Many chemical reactions are accompanied by concerted phenomena, such as variance transition, structural changes, and particle formation. Various measurement techniques are employed to understand the whole picture of such concerted phenomena. A combination of small‐angle X‐ray scattering (SAXS), X‐ray diffraction (XRD), and X‐ray absorption fine structure (XAFS) is useful for studying concerted phenomena that occur, for example, inside rechargeable batteries. This combination can cover large lengths from 1 Å to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 52 publications
4
4
0
Order By: Relevance
“…32 This partial conversion can be due to the cutoff voltage for the conversion mechanism (i.e., 1.2 V vs Li + /Li in this study) as suggested previously. 32 However, at low potentials for conversion active materials, Simon et al showed that irreversible electrolyte reduction mechanisms can occur, affecting the reversibility of the cell assembly. 40 An in-depth comprehension of the different mechanisms occurring in the cell is thus necessary in order to determine the appropriate cutoff voltage of the conversion materials.…”
Section: ■ Results and Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…32 This partial conversion can be due to the cutoff voltage for the conversion mechanism (i.e., 1.2 V vs Li + /Li in this study) as suggested previously. 32 However, at low potentials for conversion active materials, Simon et al showed that irreversible electrolyte reduction mechanisms can occur, affecting the reversibility of the cell assembly. 40 An in-depth comprehension of the different mechanisms occurring in the cell is thus necessary in order to determine the appropriate cutoff voltage of the conversion materials.…”
Section: ■ Results and Discussionsupporting
confidence: 66%
“…The reduction path followed at elevated temperatures involved the formation of FeF 2 type structure, as calculated by Doe et al 30 However, the oxidation at room temperature forming the Li x FeF 3 structure in the R3c space group differs from both reported mechanisms but has been recently observed by Gray et al and Takabayashi et al when working at room temperature with FeF 3 . 31,32 The oxidation at 80 °C formed mainly FeF 2 , as evidenced by XRD and XAS, in consistency with the mechanism proposed by Badway et al and later calculated by Doe et al 29,30 This mechanism path indicate that after a first reduction of FeF 3 , the active material is mainly reproducing a FeF 2 type (i.e., two electrons exchanged) mechanism for the following cycles of oxidation and reduction at elevated temperature, whereas at room temperature the mechanism path involves a higher number of electrons exchanged. However, it is interesting to notice that despite a lower number of exchanged electrons, the FeF 3 at higher temperature exhibits better performance than at room temperature (Figure 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations